2022
DOI: 10.3390/curroncol29050249
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Anxiety and Depression after Diagnosis of Young-Onset Colorectal Cancer: A Population-Based Cohort Study

Abstract: Given the increasing incidence of young-onset colorectal cancer (yCRC; <50 years), we aimed to evaluate the risk of depression and anxiety in individuals with yCRC in comparison to average-age-onset CRC (aCRC; ≥50 years) and to cancer-free controls, with stratification by sex. Our cohort study identified individuals (≥18 years) with CRC and cancer-free controls (10:1) matched on age and sex using population-based linked administrative health databases in British Columbia, Canada. We assessed depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Out of the included studies, six studies [ 6 , 8 , 17 , 18 , 19 , 20 ] assessed both anxiety and depression, and two studies [ 7 , 21 ] assessed depression only. Included studies were predominantly conducted in developed countries: United States ( n = 3) [ 6 , 17 , 21 ], Taiwan ( n = 2) [ 18 , 20 ], Netherlands ( n = 1) [ 19 ], Denmark ( n = 1) [ 7 ], and Canada ( n = 1) [ 8 ]. All studies used administrative health data from their respective countries as their main data source.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the included studies, six studies [ 6 , 8 , 17 , 18 , 19 , 20 ] assessed both anxiety and depression, and two studies [ 7 , 21 ] assessed depression only. Included studies were predominantly conducted in developed countries: United States ( n = 3) [ 6 , 17 , 21 ], Taiwan ( n = 2) [ 18 , 20 ], Netherlands ( n = 1) [ 19 ], Denmark ( n = 1) [ 7 ], and Canada ( n = 1) [ 8 ]. All studies used administrative health data from their respective countries as their main data source.…”
Section: Resultsmentioning
confidence: 99%
“…However, we note that, although studies were assessed to be reporting sex, as generally administrative health data do not capture gender, sex and gender terminology were conflated in half of the studies ( n = 2) [ 17 , 21 ], where the terms ‘men’ and ‘women’ (which refer to sex) were used interchangeably with ‘males’ and ‘females’ (which refer to gender), respectively. In regard to age, the majority of studies ( n = 7) [ 6 , 8 , 17 , 18 , 19 , 20 , 21 ] reported the age at the time of CRC diagnosis and one study [ 7 ] reported age at the time of the study. However, all studies varied in their reporting of age, as we observed either the reporting of mean and standard deviation or proportion according to varying age categories.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations